2014
DOI: 10.1016/j.baae.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Unpaved roads disrupt the effect of herbivores and pollinators on the reproduction of a dominant shrub

Abstract: Anthropogenic linear developments, such as trails and firebreaks, also called soft linear developments (SLD), can influence animal behavior, altering the ecological interactions in which animals are involved. For example, SLD can affect the behavior of pollinators and herbivores, but little is known about the combined effect of these three elements on plant reproduction.We evaluated the combined effect of SLD, insect pollinators and herbivores (ungulates) on three reproductive output variables (fruit set, seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…This consistent result is highly improbable if dust exposure had no effect on pollen receipt. Furthermore, the fact that we observed the same pattern with experimental hand dusting implicates dust, rather than other effects of roads or features correlated with roads (e.g., Geerts and Pauw 2011;Suárez-Esteban et al 2014), as a major (perhaps sole) cause of reduced pollen receipt.…”
Section: Discussionsupporting
confidence: 61%
“…This consistent result is highly improbable if dust exposure had no effect on pollen receipt. Furthermore, the fact that we observed the same pattern with experimental hand dusting implicates dust, rather than other effects of roads or features correlated with roads (e.g., Geerts and Pauw 2011;Suárez-Esteban et al 2014), as a major (perhaps sole) cause of reduced pollen receipt.…”
Section: Discussionsupporting
confidence: 61%
“…For example, the declining number and quality of pollinators in an area due to human activity, such as a nearby construction or a major road disrupting an area, has had an effect in other plant species, such as lower fruit set in Halimium halimifolium (L.) Willk. (Suárez-Esteban et al, 2014). Previous studies that found low levels of genetic variation in wild populations of cranberry were surprised by their low diversity results (Stewart and Excoffier, 1996;Bruederle et al, 1996).…”
Section: Vaccinium Macrocarpon Genetic Diversitymentioning
confidence: 99%
“…Species richness not exhibiting a relationship with patch area contradicts the long‐standing species–area hypothesis (Arrhenius, 1921; Gleason, 1922). In addition, previous studies have found differing effects of roads on both species' dispersal as well as gene flow (Taylor et al, 2012; Suárez‐Esteban et al, 2013, 2014; Lemke et al, 2019). We found that the area‐dependent metapopulation extinction probability (avg x values) was highest in large, regularly shaped sites, highlighting how area availability in patches may be crucial for metapopulation persistence.…”
Section: Discussionmentioning
confidence: 96%